2013
DOI: 10.1002/j.2333-8504.2013.tb02346.x
|View full text |Cite
|
Sign up to set email alerts
|

Weighting Test Samples in Irt Linking and Equating: Toward an Improved Sampling Design for Complex Equating

Abstract: Since its 1947 founding, ETS has conducted and disseminated scientific research to support its products and services, and to advance the measurement and education fields. In keeping with these goals, ETS is committed to making its research freely available to the professional community and to the general public. Published accounts of ETS research, including papers in the ETS Research Report series, undergo a formal peer-review process by ETS staff to ensure that they meet established scientific and professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…With test takers' multiple background variables that are statistically related to the test scores, such as age, gender, education, and testing experiences, the weighted equating proposed in this study can still be implemented, but with a more sophisticated weighting process. Some possibilities are propensity score matching, DAG, as in Livingston (2014), the minimum discriminant information method as in Haberman (1984), or poststratification ranking as in Qian et al (2013).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With test takers' multiple background variables that are statistically related to the test scores, such as age, gender, education, and testing experiences, the weighted equating proposed in this study can still be implemented, but with a more sophisticated weighting process. Some possibilities are propensity score matching, DAG, as in Livingston (2014), the minimum discriminant information method as in Haberman (1984), or poststratification ranking as in Qian et al (2013).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…With simulation studies based on real data, they showed that the equating based on common items could be improved by incorporating the PEG adjustment procedure into the NEAT process. With common item designs, Qian et al (2013) studied the effects of weighting test takers using item response theory (IRT) true‐score equating. They found that the scale transformation parameters for converting the item parameter estimates from one scale to another were more stable with weighted equating than with unweighted equating.…”
mentioning
confidence: 99%
“…For GJRR, a replicate sample is formed by randomly dropping one group of cases from the sample and making adjustment to weights based on statistical techniques such as minimum discriminant information adjustment (Haberman, 2015), raking, and poststratification (Qian et al, 2013). Let J be the number of total replicate samples.…”
Section: Methodsmentioning
confidence: 99%
“…Results indicated that although this procedure adjusts for group differences, it does not reduce the ability difference between the new and old form samples enough to warrant use. Qian et al (2013) used techniques for weighting observations to yield a weighted sample distribution that is consistent with the target population distribution to achieve true-score equatings that are more invariant across administrations than those obtained with unweighted samples.…”
Section: Weighted Samplesmentioning
confidence: 99%